2005
DOI: 10.1186/1471-2334-5-33
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of syphilis infection among drug addicts

Abstract: Background: Recent epidemiological data show an increased trend of official estimates for syphilis infection in the general population. Many of the infected cases remain undetected leaving an underestimation of the true prevalence of syphilis in the general population, but also among subpopulations such as illicit drug users. There is limited epidemiological data published on the proportion and risk factors of syphilis infections associated with illicit drug abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
(11 reference statements)
2
8
1
Order By: Relevance
“…This was in conformity with the findings of Todd et al (2001) who also reported higher prevalence of T. pallidum infection in women (9.1%) than in men (7.5%) in a rural African population where polygamy is common. In another study, a higher rate of infection in women with T. pallidum than men was observed with the findings of Scherbaum et al (2005) who reported that women had up to 4.5% higher prevalence of infection than men in Germany. The present finding on syphilis is almost in agreement with earlier reports in Irulas by Kanthesh et al (2004) as 4.22% and Kalaivani et al (2001) in Kolli hills Malayali tribes as 7.4%.…”
Section: Discussionsupporting
confidence: 64%
“…This was in conformity with the findings of Todd et al (2001) who also reported higher prevalence of T. pallidum infection in women (9.1%) than in men (7.5%) in a rural African population where polygamy is common. In another study, a higher rate of infection in women with T. pallidum than men was observed with the findings of Scherbaum et al (2005) who reported that women had up to 4.5% higher prevalence of infection than men in Germany. The present finding on syphilis is almost in agreement with earlier reports in Irulas by Kanthesh et al (2004) as 4.22% and Kalaivani et al (2001) in Kolli hills Malayali tribes as 7.4%.…”
Section: Discussionsupporting
confidence: 64%
“…In our study, 30 out of the 89 subjects who used drugs had a co-infection. These results highlighted the necessity of routine HCV testing for T. pallidum infected individuals [29], and also suggested that preventing syphilis should be included as a part of HBV control strategies. Targeted trainings for physicians and expanded syphilis screening services for HBV positive individuals are urgently needed [30,31].…”
Section: Discussionmentioning
confidence: 89%
“…Among women, syphilis primarily affects those who are most likely to conceive, mandating screening for syphilis antenatally. Localized outbreaks have been associated with commercial sex workers and cocaine usage [9,11,12], with an over-representation of pregnant women from ethnic minorities born outside the UK [13]. Recent studies [13,14,15 ] have raised concerns that current antenatal strategies may be inadequate in the identification and treatment of women at risk.…”
Section: Global and National Epidemiologymentioning
confidence: 99%